Controlling antibiotic usage – analysis of nationally published data from GP practices including demography, geography, comorbidity and prescribing factors highlights opportunities to reduce overall prescribing through changes in discretionary prescribing choices. (2020) - Heald, Adrian; Davies, Mark; Lunt, Mark; Fulton-McAlister, Erin; Abid, Hussain; Staa, Tjeerd Van; Anderson, Simon; Stedman, Michael
No abstract available